Pengaruh Corporate Social Responsibility dan Ukuran Perusahaan terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Moderator - Novyarni, Nelli; Aminur, Dede Rizki; Harni, Reni; Kartijo, Kartijo (Jurnal EMT KITA, 2026)
In the domestic market, companies such as PT Bukit Asam Tbk (PTBA) recorded a decline in revenue and profit in 2023 compared to the previous year due to price pressures, but remain optimistic about long-term prospects with market and production diversification strategies. This study aims to analyze the effect of Corporate Social Responsibility (CSR) and Company Size on Company Value, with Profitability as a moderating variable. The research subjects were coal mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. This study used a quantitative approach with an archival research method to analyze the effect of Corporate Social Responsibility (CSR) disclosure and company size on company value, with profitability as a moderating variable. The data used were secondary data obtained from companies' annual reports and sustainability reports published on the official Indonesia Stock Exchange website (www.idx.co.id) and the official websites of each company. The population in this study was coal mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The sample was selected using a purposive sampling method based on certain predetermined criteria. The data analysis techniques used were multiple linear regression and Moderated Regression Analysis (MRA), which were processed using EViews 13 software. The results of the study indicate that CSR Disclosure affects Company Value, Company Size affects Company Value. The influence of CSR and company size on company value is 31.56%. In addition, the effectiveness of CSR in increasing company value does not depend on the level of profitability and profitability is not always a reinforcing mechanism between company size and company value, so it does not automatically translate into increased value in the eyes of the market.